Relationship between Spraying Technique and Use of PPE (Personal Protective Equipment) With Anemia Farmers in Juhar Ginting Sadanioga Village, Karo Regency in 2018 - Imelda Yuristi; Nurmaini; Albiner Siagian (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Being poisoned by pesticide used for farming becomes public health’s problem. One of the poisoning sources is organophosphate pesticide. The impact of poisoning due to pesticides is anemia. The purpose of this study was to analyze the relationship between spraying techniques, and the use of PPE (personal protective equipment), with anemia farmers in Juhar Ginting Sadanioga Village, Karo Regency in 2018. The research method used was cross sectional in Juhar Ginting Sadanioga Village, Karo Regency with a total sample of 61 people obtained by Simple Random Sampling. Data were obtained through interviews with questionnaires and examination of hemoglobin levels using a portable hemoglobin meter. The study found that spraying techniques were not good (p = 0.033), and the use of PPE was not good (p = 0.025) relationship with anemia. It’s suggested to farmers should pay more attention to the direction of the wind, long time spraying/ day, spraying doses, and in the use of PPE that meets the requirements to reduce the risk of pesticide exposure.